Motivated Memory in Dictator Games - Charlotte Saucet; Marie Claire Villeval (Institute of Labor Economics (IZA), 2018)
The memory people have of their past behavior is one of the main sources of information about themselves. To study whether people retrieve their memory self-servingly in social encounters, we designed an experiment in which participants play binary dictator games and then have to recall the amounts allocated to the receivers. We find evidence of motivated memory through selective recalls: dictators remember more their altruistic than their selfish choices. A causal effect of the responsibility of decisions is identified, as the recall asymmetry disappears when options are selected randomly by the computer program. Incentivizing memory accuracy increases the percentage of dictators' correct recalls only when they behaved altruistically. In contrast, there is no clear evidence of motivated memory through biased, i.e., overly optimistic recalls: dictators recall selectively but they do not bias strategically the direction and magnitude of these recalls.
Keywords: C91; D91; D63; D64; 330; motivated memory; selective recall; self-image; Dictator Game; experiment